Model of Multicultural Education In Religion As A Strengthening Strategy The Character of Tolerance In Early Childhood - Finadatul Wahidah; Dewi Maristyawati (STAIFAS-Press, 2023)
Multiculturalism is a nation's priceless wealth, as a potential that must be developed and fostered; otherwise, if this diversity is not developed and nurtured correctly, it will grow into something frightening that impacts intolerance between communities. This research was conducted in formal institutions at the early childhood level. This study uses a qualitative approach. Data collection techniques using observation, interviews, and documentation. Data analysis techniques use the theory of Miles and Huberman, namely data condensation, data presentation, and inference. This research concludes that the multicultural model in religion can be implemented in three forms: Content Integration, Equitable Pedagogy, and Empowering School Culture and Social Structure. First, this Content Integration can be carried out with the learning center model by providing examples that occur in everyday life from various points of view; this activity is structured in three stages: opening, core, and closing. Second, in applying equitable pedagogical education, namely praying according to their respective beliefs, there is no difference between Muslim and non-Muslim students. Still, activities that contain religious elements are carried out differently. Third, in applying cultural empowerment, empowering school culture and the social structure includes routine and exemplary habituation activities.